Telemedicine Technology Application for COVID-19 Patient Tracing Using Smartphone GNSS - Cahyadi, M. N. (Geoinformatics International, 2022)
In order to cope with a pandemic COVID-19, Indonesia has implemented various measures of public health including contact tracing. This research will integrate three aspects, namely the use of telemedicine for geographic information system, tracking COVID-19 patients using smartphones and diagnosed persons. The three aspects are wrapped in interactive and informative application where users can track their journeys, and communicate directly with the doctors. The geographic information system was built based on statistical analysis of the coronavirus disease (COVID-19) pandemic to determine the factors that affect the number of COVID-19 patients in an area using geographically weighted regression. Later on, this application can provide information about the current conditions, increase data transparency, and used as a tool in assessing a particular policy. This telemedicine application utilizes a map-based geographic information system (GIS) feature to display information. This system also has high security so that it can protect user information and can be accessed easily by users. © Geoinformatics International.